REVIEW: Language contact and vocabulary enrichment: Scandinavian elements in Middle English. By Isabel Moskowich, Frankfurt am Main: Peter Lang, 2012. Pp. 173. - Fekete, Tamás (Studia Anglica Posnaniensia, 2014)
Review: Language contact and vocabulary enrichment: Scandinavian elements in Middle English. By Isabel Moskowich, Frankfurt am Main: Peter Lang, 2012. Pp. 173.